The tomato plastidic fructokinase SlFRK3 plays a role in xylem development. Issue 4 (15th October 2015) - Stein, Ofer; Damari‐Weissler, Hila; Secchi, Francesca; Rachamilevitch, Shimon; German, Marcelo A.; Yeselson, Yelena; Amir, Rachel; Schaffer, Arthur; Holbrook, N. Michele; Aloni, Roni; Zwieniecki, Maciej A.; Granot, David
Summary: Plants have two kinds of fructokinases (FRKs) that catalyze the key step of fructose phosphorylation, cytosolic and plastidic. The major cytosolic tomato FRK, SlFRK2, is essential for the development of xylem vessels. In order to study the role of SlFRK3, which encodes the only plastidic FRK, we generated transgenic tomato ( Solanum lycopersicon ) plants with RNAi suppression of SlFRK3 as well as plants expressing beta‐glucoronidase (GUS) under the SlFRK3 promoter. GUS staining indicated SlFRK3 expression in vascular tissues of the leaves and stems, including cambium, differentiating xylem, young xylem fibers and phloem companion cells. Suppression of SlFRK3 reduced the stem xylem area, stem and root water conductance, and whole‐plant transpiration, with minor effects on plant development. However, suppression of SlFRK3 accompanied by partial suppression of SlFRK2 induced significant growth‐inhibition effects, including the wilting of mature leaves. Grafting experiments revealed that these growth effects are imposed primarily by the leaves, whose petioles had unlignified, thin‐walled xylem fibers with collapsed parenchyma cells around the vessels. A cross between the SlFRK2 ‐antisense and SlFRK3 ‐RNAi lines exhibited similar wilting and anatomical effects, confirming that these effects are the result of the combined suppression of SlFRK3 and SlFRK2 . These results demonstrate a role of the plastidic SlFRK3 in xylem development and hydraulic conductance.